PENGUATAN KESIAPSIAGAAN BENCANA TANAH LONGSOR: KOLABORASI MAHASISWA, PEMERINTAH DESA, DAN MASYARAKAT - Fitri Adi Setyorini; Muhammad Aris Pujiyanto; Anggi Fitria Cahyaningsih (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This community service program aimed to improve the preparedness of the residents of Kemawi Village, Somagede District, Banyumas Regency toward the potential risk of landslides. Kemawi Village has hilly topography, high rainfall intensity, and considerable vulnerability to landslides, making efforts to enhance community understanding of disaster mitigation highly necessary. The program was implemented through disaster awareness socialization and participatory Focus Group Discussions (FGDs) involving local residents, village officials, community leaders, and community organizations. The activities covered topics such as early signs of landslides, early warning systems, evacuation routes, and simple community-based mitigation measures. Through these activities, the community demonstrated improved understanding of disaster preparedness and was able to identify landslide-prone areas and formulate mitigation measures based on local conditions. This community service activity is expected to strengthen community capacity in building disaster preparedness and support the development of a sustainable disaster-resilient community.